Peran Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah Kabupaten Ciamis terhadap Peraturan Daerah - Maha Shania Tara Gusmoi; Siti Soleha; Gina Mardiana; Regi Refian Garis (Public Administration Dept, Faculty of Social and Political Science, 2023)
This article explains how the DPRD carries out its regulatory oversight duties. The purpose of this research is to find out how well Regional Regulations are implemented based on the prevailing laws and regulations. Local Regulations and Regulations of Regents/Mayors are subject to DPRD supervision. Enforcement of Local Regulations is an important part of the governance structure. Hearings, working visits, formation of committees, etc. are just some of the ways in which the DPRD carries out its supervisory role. The purpose of this oversight is to ensure that local governments follow plans and laws when implementing their initiatives. The author used a qualitative approach, conducting on-site observations, to collect information and data for this study. The data analysis shows that each Local Regulation is formed by the Regent or DPRD upon mutual consent.